BUDAYA 3S (SENYUM, SALAM, SAPA) SEBAGAI IDE PENCIPTAAN KARYA LUKIS - Berry Pranata, Drs. Erfahmi, M.Sn., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of making these art works was for visualizing the smartphone’s bad influence in these final art works painting contemporary. The 3S culture was as idea in these final art works was as information media to society. so that it could know the 3S culture. In order that willingness for apply in this life. The method for realizing ideas was: Preparing, elaborasi stage, synthesis stage, realization stage, concept realization and finishing stage. These final works described about the lessness influence was getting developing communication meda as smartphone that it over used. Because The result taking and the stage created 10 works that giving motivation, inspiration, information, and learning media for creating a human being that have character in their life.Keywords : Culture, Idea, Painting.